MANAJEMEN ORGANISASI BADAN WAKAF UANG MUHAMMADIYAH (BWUM) SUMATERA BARAT TINJAUAN PENGORGANISASIAN - Thaheransyah Thaheransyah; Lidya Komala sari (Universitas Islam Negeri Imam Bonjol Padang, 2020)
Badan Wakaf Uang Muhammadiyah (BWUM) West Sumatra is a cash waqf management body by collecting, developing and utilizing the proceeds / surplus of waqf. This study aims to reveal how the process of organizing the BWUM West Sumatra. This type of research is field research, using qualitative methods through a descriptive approach, namely a problem-solving procedure that is investigated by describing or describing the object of research based on the facts that appear as they are. The data sources used are primary data and secondary data from BWUM West Sumatra. The results of this study indicate that the work grouping has been carried out by BWUM West Sumatra, the management assigns jobs based on their abilities and expertise. This work grouping determines the plan of activities to be carried out by the executive through deliberation. Regarding the delegation of authority and responsibility given to the executive, it is determined by the division of labor according to their respective fields. But in its implementation there are still managers who have concurrent positions in carrying out tasks, there are managers who overlap the tasks they are assigned, then there are administrators who are inactive during the management period even though there is a change in management structure. Meanwhile, the working relationship carried out by the BWUM West Sumatra management is not concerned with the success of their own duties, because progress in one area will not give meaning without being accompanied by others in the management of BWUM West Sumatra.